A host-specific diaminobutyrate aminotransferase contributes to symbiotic performance, homoserine metabolism, and competitiveness in the Rhizobium leguminosarum/Pisum sativum system - Ballesteros-Gutiérrez, Marta; Albareda, Marta; Barbas, Coral; López-Gonzálvez, Ángeles; Dunn, Michael F.; Palacios, José M. (Frontiers in Microbiology, 2023)
Rhizobium leguminosarum bv. viciae (Rlv) UPM791 effectively nodulates pea and lentil, but bacteroids contain a number of proteins differentially expressed depending on the host. One of these host-dependent proteins (C189) is similar to a diaminobutyrate-2-oxoglutarate aminotransferase (DABA-AT). DABA-AT activity was demonstrated with cell extracts and with purified protein, so C189 was renamed as Dat. The dat gene was strongly induced in the central, active area of pea nodules, but not in lentil. Mutants defective in dat were impaired in symbiotic performance with pea plants, exhibiting reduced shoot dry weight, smaller nodules, and a lower competitiveness for nodulation. In contrast, there were no significant differences between mutant and wild-type in symbiosis with lentil plants. A comparative metabolomic approach using cell-free extracts from bacteroids induced in pea and lentil showed significant differences among the strains in pea bacteroids whereas no significant differences were found in lentil. Targeted metabolomic analysis revealed that the dat mutation abolished the presence of 2,4-diaminobutyrate (DABA) in pea nodules, indicating that DABA-AT reaction is oriented towards the production of DABA from L-aspartate semialdehyde. This analysis also showed the presence of L-homoserine, a likely source of aspartate semialdehyde, in pea bacteroids but not in those induced in lentil. The dat mutant showed impaired growth when cells were grown with L-homoserine as nitrogen source. Inclusion of DABA or L-homoserine as N source suppressed pantothenate auxotropy in Rlv UPM791, suggesting DABA as source of the pantothenate precursor -alanine. These data indicate that Rlv UPM791 Dat enzyme is part of an adaptation mechanism of this bacterium to a homoserine-rich environment such as pea nodule and rhizosphere